U-Pb Geochronology Using 193 nm Excimer LA-ICP-MS Optimized for In Situ Accessory Mineral Dating in Thin Sections - McFarlane, Chris; Luo, Yan (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2012)
SUMMARY This article is designed to provide a synopsis of the application of LAICP-MS to U-Pb geochronology of accessory minerals, in standard polished thin sections, using modern 193 nm ArF excimer laser ablation (LA) and quadrupole inductively coupled plasma mass spectrometry (Q-ICP-MS) instrumentation. During about the last five years, Q-ICP-MS manufacturers (e.g. Agilent, Thermo Scientific, Perkin Elmer, Bruker Daltonics) have introduced new instruments or interfaces with higher sensitivity and lower backgrounds, compared to the previous generation of instruments. ArF excimer laser systems built by Resonetics (RESOlution™ M-50 and S-50), NewWave Research (NWR-193™), Photon Machines (Excite™ and Analyte G2™), and Coherent (GeoLas™), have also expanded their capabilities in a relatively short period of time. There has also been a significant leap in software development and laser control, which, when matched with sophisticated offline data processing has increased the overall efficiency of the technique. This article begins with a background section designed to provide the basic bibliography and theory of laser-target interaction for nanosecond and femtosecond lasers. We then describe enhancements in ICP-MS sensitivity, the importance of the laser-ablation cell, smoothing devices, and synchronized hardware and software controls. We also provide examples of how these recent advances have dramatically increased the efficiency (e.g. cost per analysis), precision and accuracy of in situ U-Pb geochronology of accessory minerals using 193 nm excimer LA-ICP-MS. Demonstration datasets are based on the instrumentation installed at the University of New Brunswick, and provide examples of the general capabilities of excimer LAICP-MS for detailed in situ U-Pb geochronology.